2018
DOI: 10.1093/jpepsy/jsy097
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Behavioral Intervention Technologies for Youth With Chronic Health Conditions and Physical and Intellectual Disabilities: Implications for Adolescents and Young Adults With Spina Bifida

Abstract: Objective Behavioral intervention technologies (BITs) stand as a promising delivery mechanism that overcomes multiple condition-specific and access barriers for self-management interventions for adolescents and young adults with spina bifida (AYA-SB). The purpose of the current review was to synthesize the behavioral and self-management intervention literature in conditions that have overlapping symptoms with youth with SB and to develop a model of likely user needs for AYA-SB that promotes self-management. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…The evaluated elements of My Diet Coach involved active, text-based data entry. Consistent with the literature on AYAs with similar symptom profiles [16], the AYA-SB participants reported that these elements could be improved for their use by having tutorials, being simpler, and having less logging options. Possibly because of the lack of such features and/or the executive functioning problems associated with SB [23], participants also displayed several errors for a relatively simple data entry path.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…The evaluated elements of My Diet Coach involved active, text-based data entry. Consistent with the literature on AYAs with similar symptom profiles [16], the AYA-SB participants reported that these elements could be improved for their use by having tutorials, being simpler, and having less logging options. Possibly because of the lack of such features and/or the executive functioning problems associated with SB [23], participants also displayed several errors for a relatively simple data entry path.…”
Section: Discussionsupporting
confidence: 74%
“…Although the current findings suggest that My Diet Coach is learnable for AYA-SBs, it also implicates personalizing existing elements and characteristics for AYA-SBs and related users (eg, youth with physical and/or motor disabilities) [16]. The evaluated elements of My Diet Coach involved active, text-based data entry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations